THE ECONOMIC ACTIVITIES AND INDUSTRIAL SPATIAL CONCENTRATION IN REGENCIES/CITIES IN CENTRAL JAVA PROVINCE IN 2000-2013 - Fitria Nur Rahmawati; Tri Mulyaningsih (MESP–FEB UNS, 2019)
This study aimed to identify the pattern of the industrial spatial concentration and its stability in Central Java between 2000 and 2013. Industrial spatial concentration analysis is conducted in the Provincial Coordination Board (Bakorwil) in Central Java Province. This study employed the industrial concentration ratio and Geographic Information Systems (GIS). The data of employment of the National Labor Force Survey (Sakernas) were used to examine the industrial concentration in the province. This research found that industries in Central Java province concentrated on agriculture and manufacturing. The agricultural industry is a resource-based industry spatially concentrated in regencies. The manufacturing industry is a foot-loose industry, which does not have specific location patterns. In other words, the industry can be located in both regencies and cities. Service industries such as trade, communications, and finance industries are spatially concentrated in the cities because they are market-oriented. Finally, the competitiveness of tobacco manufacturing industry (Code: 160) in Kudus, the industry of wood products, and woven goods from rattan, bamboo and other similar materials (Code: 202) in Kebumen, furniture industry (Code: 361) in Jepara, and mobile retail trading/outside building (Code: 525) in Tegal City sustained in the past ten years.Keywords: Industrial Spatial Concentration, Bakorwil in Central Java Province, Geographic Information Systems (GIS)